2022
DOI: 10.1021/acs.macromol.1c02262
|View full text |Cite
|
Sign up to set email alerts
|

When Polymer Chains Are Highly Aligned: A Perspective on Extensional Rheology

Abstract: We provide a Perspective on recent findings in extensional rheology for polymer melts and solutions with different macromolecular architectures. For linear polymer systems, we focus on the argument of flow-induced friction reduction and provide our comments from an experimental point of view. For branched polymers, we provide our understanding on how to control extensional viscosity for polymers with different zero-shear-rate viscosity based on recent experimental results of star and comb polymer melts. For ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 99 publications
3
26
0
Order By: Relevance
“…In addition, the FENE effect leads to the transient strain hardening for all samples in this study, but not the thickening of η E as seen in the unentangled PS and PtBS melts. 21 This lack of thickening behavior is also seen for other linear entangled polymers, 17,18 probably because the nonlinearity stemming from the disentanglement mechanisms overwhelms the hardening due to the FENE effect.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the FENE effect leads to the transient strain hardening for all samples in this study, but not the thickening of η E as seen in the unentangled PS and PtBS melts. 21 This lack of thickening behavior is also seen for other linear entangled polymers, 17,18 probably because the nonlinearity stemming from the disentanglement mechanisms overwhelms the hardening due to the FENE effect.…”
mentioning
confidence: 92%
“…9−15 For example, Hassager and co-workers observed strain-thinning behavior of the steady elongational viscosity η E ∼ εḢ −0.5 for the polystyrene melt, even when Wi R is larger than one. 16 To bridge the behavior of the entangled polymer melts and solutions, Huang et al 17,18 systematically changed the concentration of polystyrene dissolved in the oligomeric styrene (OS), but kept the number of entanglements per chain, N/N e , to be the same. They observed that LVE can be properly normalized using the plateau modulus G N and the segmental time τ 0 as the vertical and horizontal normalization parameters.…”
mentioning
confidence: 99%
“…Another topologically distinct location in PMMA is the side chain of the polymer. With the indication that thermal, mechanical, and rheological behavior is affected by the presence and properties of side chains, we expected the side chain of PMMA to be affected differently by vitrification compared to other polymer compartments. Indeed, the p-SC sample containing SP in the side chain, a location with high steric congestion, showed a strikingly different photochemical behavior compared to the other PMMA samples: the introduction of SP to the polymer side chain led to the partial reversal of the photochemical reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, DNA polymers cluster at the leading edge of the moving probe, increasing the local entanglement density and forming a wake in the strain path. Threading events, which are most pervasive in the 0.65:0 blend, reduce this clustering by facilitating stretching and alignment which, in turn, reduce polymer buildup at the leading edges 51,[86][87][88] . Reduced threading probability in the 0.5:0 and 0.5:6.4 systems leads to weaker thinning and more polymer buildup, as shown in Fig.…”
Section: Threading Of Dna Rings In Entangled Ring-linear Blends Leads...mentioning
confidence: 99%